Proteome-based investigation of O-GlcNAcylation in a C. elegans model of ageing and Alzheimer’s disease: Functional support for earlier hypothesis-generating findings - Fernando Garcia Olivera (PLoS ONE, 2026)
O-linked N-acetylglucosamine (O-GlcNAc) is a post-translational modification of serine and threonine residues on nuclear and cytoplasmic proteins. The identity of O-GlcNAcylated proteins during ageing and neurodegenerative disease remains incompletely defined. Thus, animal models play a crucial role for the systematic characterization and cataloguing of O-GlcNAc-modified proteins. In this study, proteomic analysis was performed to identify O-GlcNAc-modified proteins in both L1 larval and adult stages of wild-type N2 and of aex-3 p::Tau(V337M) transgenic Caenorhabditis elegans , a nematode model of ageing and Alzheimer’s disease (AD) using high-resolution nano-LC–ESI mass spectrometry. O-GlcNAcylated proteins identified in the N2 strain were mapped to nuclear- and RNA-related processes in both stages. In the tau-expressing strain, functional enrichment analysis of the identified proteins indicated a predominance of stress-response–related pathways. Together, these data present an analysis of O-GlcNAc-modified proteins across early development, adulthood, and a tau-related C. elegans model, providing a resource for future functional and comparative studies of O-GlcNAcylation in ageing and AD.